99.6k views
0 votes
72.3 + (-39.1)



Rewrite the expression by breaking up each of the place values. In this case, the place values are tens, ones, and tenths.

User Guy Yogev
by
5.0k points

2 Answers

4 votes

Answer:

72.3 - 39.1 = 70 + 2 + 0.3 + (-30) +(-9) + (0.1)

Explanation:

got it from edmentum

User Rodrigo Almeida
by
5.7k points
1 vote

Answer:

72.3 - 39.1 = 4tens - 7ones + 2tenth

Explanation:

Give the expression 72.3 + (-39.1)

opening the parenthesis:

= 72.3 + (-39.1)

= 72.3 - 39.1

Breaking the decimal values into place values

72.3 = 7tens + 2units + 3tenth

72.3 = 7(10)+2(1)+3(1/10)

72.3 =70+2+0.3

Similarly for 39.1

39.1 = 3tens + 9units + 1tenth

39.1 = 3(10)+9(1)+1(1/10)

39.1 =30+9+0.1

72.3 - 39.1 = 70+2+0.3 - (30+9+0.1)

72.3 - 39.1 = 70+2+0.3 - 30-9-0.1

72.3 - 39.1 = 70-30+2-9+0.3-0.1

72.3 - 39.1 = 40 - 7 +0.2

72.3 - 39.1 = 4tens - 7ones + 2tenth

User Ckuessner
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.